Asylees, refugees or entrants: the case of the peruvian embassy in Havana in 1980 - Pinto-Bazurco Rittler, Ernesto (2023)
In order to preserve the life and physical integrity of approximately 10,000 Cubans who were seeking to leave their country, in 1980 the head of the Peruvian diplomatic mission managed to successfully negotiate a peaceful and practical solution with the Castro government. This solution was based on the application of an exceptional legal category, but closely related to the figure of asylum and refugee, called entrant. Eventually, the Peruvian proposal allowed the massive departure of more than 120 thousand Cubans through the port of Mariel. By superimposing the protection of the person above any migratory qualification, we maintain that it will be possible to facilitate pragmatic solutions for current (Ukraine) and upcoming issues (famine) on the displacement of people.